The personal history of Rachel Dupree : [a novel] - Weisgarber, Ann (Penguin, 2011)
It is 1917 in the South Dakota Badlands and the summer has been hard. Rachel and Isaac DuPree had left Chicago fourteen years ago to stake their claim. Isaac, a former Buffalo Soldier, is fiercely proud: black families are rare in the West, and black ranchers even rarer. But it hasn't rained in months, the cattle are bellowing with thirst, and supplies have dwindled. Struggling to feed her family, Rachel is isolated by more than just geography. She is determined to give her surviving children the life they deserve, but Isaac will never leave his ranch: land means a measure of equality with the white man. Rachel must find the strength to do what is right--for her children, for her husband, and for herself.